Analysis of Market Concentration in the Borsa Istanbul BIST 10 Index Using the Herfindahl-Hirschman Index - Çetinkaya, Reşit (Bilgicagi Education Consulting and Publishing Industry Trade Limited Company, 2025)
The process of closing the account transactions related to the purchase and sale of shares on the stock exchange through reconciliation between the buyer and seller is called "settlement". The settlement process takes place two trading days after the transaction, on the “T+2” day. The study covers the top 10 stocks on the Borsa Istanbul (BIST), excluding liquid banks. The monthly clearing shares of all brokerage firms trading these stocks between August (2024-2025) were obtained from the Matriks IQ data terminal, and the concentration of brokerage firms on the stocks and the competitive levels of the stocks were analyzed using the Herfindahl-Hirschman Index (HHI). The analysis revealed that the stocks with low concentration and high competition are EKGYO, EREGL, KCHOL, SASA, THYAO, and TUPRS. Stocks with medium concentration and competition, but where a few brokerage firms have higher shares in the clearing shares, were found to be ASELS, BIMAS, SAHOL, and TCELL. No stock was identified in the analysis result with a high HHI value indicating high concentration and limited competition. In conclusion, changes in brokerage firms' trading shares are important in terms of companies' market valuation. Analysis using the HHI index can be used as a tool for investors and market regulators to establish the existence of competition and measure market dynamics.